Propuesta de manejo ambiental para recuperar la cuenca del morona, debido a la contaminación por actividades de hidrocarburos - Sáenz Sánchez, César Augusto (2008)
The work suggests a proposal that it assures the environmental handling of the waters of the basin of the river Morona, due to the contamination for oil activities. It was characterized physical and chemically the bodies of water in situ and in the laboratories of the National University of the Peruvian Amazonía. The sample picked up in growing, he/she mediates growing and low water, they report securities that you/they surpass the Permissible Maximum Limits, as the Dissolved Oxygen, Oil and Fatty, Cadmium, Barium and Dioxide of Carbon that determine the degradation of the biomass, committing the deterioration of the atmosphere and consequently, irreversible damages to the ecosystem of the basin. Poverty, illnesses endemic and alarming illiteracy exists. Being almost noticed the disappearance of the fish and other aquatic species that constitute the daily sustenance of the inhabitants of these communities. The proposal of environmental handling, represents a contribution to the scientific knowledge on hydrological, climatic, environmental, social, economic and cultural topics, impacting, overalls, in the contamination caused by the exploitation and oil exploration in the area. The data of the diagnosis, help to formulate proposals, outlining decontamination stocks and improvements to the ecosystem, to optimize, fundamentally, the conditions in that the indigenous communities of the basin of the river live Morona.